SIMBOL-SIMBOL PERJUANGAN KELAS PEKERJA DI AMERIKA DALAM NOVEL WHITE FANG KARYA JACK LONDON - Firdaus Kurniasih, Elina Aenil (Sabda: Jurnal Kajian Kebudayaan, 2016)
White Fang is a novel containing the idea of working class strugle, but this idea is hidden behind the symbols found in its characters. The writer found that the dogs in this novel is a symbol of working class, while the men as the symbol of bourgeois. Class symbols are bounded by other symbols such as meat, fire, stick, and rope as the power of bourgeois. The writer also found the relation of dominance-submission and oppresssuppressed between bourgeois and proletariat which cause a class that has to struggle agains another class. The solution of this problem is emphasised to the bourgeois class that should be just to their workers.